Correction to: Genetic Architecture and Signatures of Selection in the Caqueteño Creole (Colombian Native Cattle) (Diversity, (2022), 14, 10, (828), 10.3390/d14100828) - Toro-Ospina, Alejandra M.; Herrera Rios, Ana C.; Bizarria Santos, Wellington [UNESP]; Pimenta Schettini, Gustavo; Vallejo Aristizabal, Viviana H.; Tovar Claros, Gilberto; Morea, Edna Gicela Ortiz (MDPI, 2024)
In the original publication [1], the following reference [40] was not included in some sections. The citation has now been inserted in “Introduction, paragraph 3” and “Materials and Methods, 2.3. Genetic Structure of the Population”. References in the original article have been rearranged. Maiorano, A.M.; Lourenco, D.L.; Tsuruta, S.; Ospina, A.M.T.; Stafuzza, N.B.; Masuda, Y.; Filho, A.E.V.; dos Santos Goncalves Cyrillo, J.N.; Curi, R.A.; de Vasconcelos Silva, J.A., II. Assessing Genetic Architecture and Signatures of Selection of Dual Purpose Gir Cattle Populations Using Genomic Information. PLoS ONE 2018, 13, e0200694. https://doi.org/10.1371/journal.pone.0200694. To more thoroughly describe the existing literature on cattle genetics, we adjusted the following sentences. The details are provided below. A correction has been made to paragraph 3: The corrected text appears below: We added the sentence “a similar approach utilized in our previous study with the Gir cattle breed [17]” after “principal component analysis (PCA) and discriminant analysis of principal component (DAPC) were performed using the adegenet v.2.1.7 package for R software [26]”. The authors state that the scientific conclusions are unaffected. This correction was approved by the Academic Editor. The original publication has also been updated.